Steel Structures Design for Lateral and Vertical Forces, Second Edition - Williams, Alan; McGraw-Hill eBooks (New York, N.Y. : McGraw-Hill Education, 2016)
A fully updated, hands-on guide to the design of steel structures.
10.5 Prying Action -- 10.6 Bolt Group Eccentrically Loaded in Plane of Faying Surface -- 10.7 Bolt Group Eccentrically Loaded Normal to the Faying Surface -- References -- Problems -- 11 Design of Welded Connections -- 11.1 Introduction -- 11.2 Weld Types -- 11.3 Available Strength of Fillet Welds -- 11.4 Weld Group Eccentrically Loaded in Plane of Faying Surface -- 11.5 Weld Group Eccentrically Loaded Normal to Faying Surface -- References -- Problems -- 12 Plate Girders -- 12.1 Introduction -- 12.2 Girder Proportions -- 12.3 Postbuckling Strength of the Web -- 12.4 Design for Shear with Unstiffened Web -- 12.5 Design for Shear with Stiffened Web: Tension Field Action Excluded -- 12.6 Design for Shear with Stiffened Web: Tension Field Action Included -- 12.7 Design of Transverse Stiffeners -- 12.8 Flexural Design of Plate Girders -- 12.9 Design of Bearing Stiffeners -- References -- Problems -- 13 Composite Members -- 13.1 Introduction -- 13.2 Encased Composite Columns -- 13.3 Filled Composite Columns -- 13.4 Encased Composite Beams -- 13.5 Composite Beam with Flat Soffit Concrete Slab -- 13.6 Formed Steel Deck with Ribs Perpendicular to Beams -- 13.7 Formed Steel Deck with Ribs Parallel to Beams -- References -- Problems -- 14 Design of Steel Structures for Lateral Loads -- 14.1 Introduction -- 14.2 General Considerations -- 14.3 Concentrically Braced Frames -- 14.4 Ordinary Concentrically Braced Frames -- 14.5 Special Concentrically Braced Frames -- 14.6 Eccentrically Braced Frames -- 14.7 Special Moment Frames -- References -- Problems -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y.
Includes bibliographical references and index.
Also available in print edition.
Electronic reproduction.
Mode of access: Internet via World Wide Web.
In English.
Description based on e-Publication PDF.
Keywords: Steel, Structural; Structural engineering; Load factor design; Building, Iron and steel; Electronic books